(untitled) (EDUCATION IN THE 21ST CENTURY, 2025)
This paper picks up the thread of the authors’ research from our previous papers inquiring into the disempowerment and subsequent disillusion of the Black aspirants to a significant role in the UK’s teaching profession. Having tracked the situation in Liverpool [Boyle & Charles 2011, 2016] we decided to look at the capital and selected one of the London Authorities as an alternative location. We selected Newham principally because the Authority is reported to have the most ethnically diverse teaching population in the thirty-three London Authorities [Demie & Hau 2022:]. The aim of the research was to survey the self-reported experiences of Newham’s current Black teachers [i] through their own journeys as Black students in the UK schooling system and then [ii] as Black teachers working within the UK schooling system.